Chemical blackening process of stainless steel and application

Through the chemical blackening process of stainless steel, a blackening coating with good optical and electromagnetic characteristics is formed, which solves the problems of degradation of imaging quality and weakening of detection accuracy in complex environments of existing materials, and achieves efficient light control and signal reflection.

CN119824403AActive Publication Date: 2025-04-15SHENGZHEN KINHU ELECTROPLATING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510307623.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-15
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

In applications such as camera modules and millimeter-wave radar, existing materials are difficult to meet the high requirements of light control and signal reflection, especially in complex environments, their performance will be affected, resulting in a decrease in imaging quality and a weakened detection accuracy.

Method used

A chemical blackening process of stainless steel is adopted, and a uniform, dense blackening coating with good optical and electromagnetic characteristics is formed through ultrasonic-assisted alkaline oil removal, activation, sensitization and electrochemical plating. The process includes de-oiling under 40-50kHz ultrasonic, 55-65°C, activation and sensitization at room temperature, and subsequent plating in a plating solution of 90-92°C, controlling the pH value between 4.8-5.2.

Benefits of technology

The stray light suppression rate and millimeter wave reflection efficiency are significantly improved, imaging clarity and detection accuracy are improved, and the stability and durability of the blackened layer are significantly improved in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of material surface treatment, and particularly discloses a chemical blackening process of stainless steel and application. The chemical blackening process of the stainless steel comprises the following steps: removing oil from a stainless steel workpiece, and then sequentially carrying out activating treatment and sensitizing treatment; the plating solution comprises nickel sulfate, sodium hypophosphite, sodium citrate and carbon nanotubes, the pH value of the plating solution is controlled to be 4.8-5.2, the temperature is 90-92 DEG C, the workpiece is placed in the plating solution, and the blackened stainless steel workpiece is obtained after plating is conducted for 1-2 hours. The chemical blackening process of the stainless steel can be used for camera module shielding type components and millimeter wave radar reflection type components, and has the advantages of being high in stray light inhibition rate, high in millimeter wave reflectivity and high in coating durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of material surface treatment, and more specifically, to a chemical blackening process and application of stainless steel. Background Art

[0002] In the field of camera modules, light control has a great impact on imaging effects. Once stray light invades, a halo will appear in the image, just like a hazy veil covering the picture, blurring the details; the contrast is reduced, the distinction between light and dark parts is no longer clear, and the picture lacks a sense of hierarchy. The traditional shielding materials currently used have poor light absorption performance and cannot effectively block stray light. In complex environments such as high temperature, high humidity, and strong ultraviolet rays, they are prone to aging and deformation. The durability is greatly reduced, and it is difficult to meet the market demand for ever-increasing requirements for imaging quality.

[0003] Millimeter-wave radar is widely used in intelligent transportation, autonomous driving, security monitoring and other fields. Its detection accuracy and distance depend on the reflection and orientation capabilities of the reflective components to millimeter-wave signals. However, the reflection characteristics of existing materials have shortcomings. Faced with the ever-increasing requirements for high-precision detection, the reflection characteristics of existing materials will be weakened and affected to varying degrees in harsh environments such as extreme cold, extreme heat, and dust, which seriously restricts the application and expansion of millimeter-wave radar.

[0004] Stainless steel has become a high-quality substrate for manufacturing these two types of components due to its advantages such as high strength, corrosion resistance and stable performance. However, the optical and electromagnetic properties of the original stainless steel surface are difficult to meet the strict control of light by the camera module and the high requirements of signal reflection by the millimeter-wave radar. It is urgent to optimize its surface properties through a special blackening process, so as to promote further development and breakthroughs in related technologies. Summary of the invention

[0005] In order to provide a stainless steel surface blackening process suitable for camera module shielding components and millimeter wave radar reflection components, the present application provides a stainless steel chemical blackening process and application.

[0006] The chemical blackening process of stainless steel provided in this application adopts the following technical solution: A chemical blackening process for stainless steel comprises the following steps: Place the stainless steel workpiece in a solution containing a surfactant and an alkaline additive for degreasing, and treat it at 40-50kHz ultrasonic waves and 55-65℃ for 15-30 minutes; Immerse the degreased workpiece in the activation solution for 40-50 minutes at room temperature, then put the workpiece into the sensitizing solution for 40-60 minutes at 60-80℃; The plating solution comprises nickel sulfate, sodium hypophosphite, sodium citrate and carbon nanotubes. The pH value of the plating solution is controlled at 4.8-5.2 and the temperature is 90-92° C. The workpiece is placed in the plating solution and a blackened stainless steel workpiece is obtained after plating for 1-2 hours.

[0007] By adopting the above technical solution, ultrasonic assisted alkaline degreasing is used, and the treatment is carried out for 15-30 minutes under 40-50kHz ultrasonic and 55-65℃ conditions. The cavitation effect generated by ultrasonic waves can effectively remove the oil stains tightly attached to the stainless steel surface. The alkaline additive undergoes a saponification reaction with the oil stains, converting the grease into a water-soluble substance, and the surfactant further reduces the interfacial tension between the oil stains and the stainless steel surface, making the oil stains easier to detach. Thorough degreasing provides a clean and pollution-free surface for subsequent activation, sensitization and chemical plating. Soaking in the activation solution for 40-50 minutes at room temperature can form micro-pits on the stainless steel surface and increase active sites. These micro-pits greatly increase the specific surface area of ​​the stainless steel surface, allowing the reactants to contact and react more fully during the subsequent sensitization and chemical plating process. Soaking in the sensitizing solution at 60-80℃ for 40-60 minutes can adsorb catalytically active tin ions on the surface, providing catalytic centers for chemical plating. The pH value of the plating solution is controlled at 4.8-5.2, the temperature is 90-92°C, and the plating is performed for 1-2 hours. Under this condition, the nickel sulfate, sodium hypophosphite, sodium citrate and other components in the plating solution can undergo a stable chemical reaction. Sodium hypophosphite reduces nickel ions to form a coating, and sodium citrate stabilizes the nickel ions in the plating solution to prevent them from precipitating prematurely. The appropriate pH value and temperature ensure the stability of the plating solution and the high efficiency of the reaction, thereby obtaining a uniform, dense black coating with good optical and electromagnetic properties.

[0008] Optionally, the plating solution components include 25-35 parts of nickel sulfate, 20-30 parts of sodium hypophosphite, 10-15 parts of sodium citrate, 2-6 parts of carbon nanotubes, and 400-600 parts of deionized water in parts by weight.

[0009] By adopting the above technical scheme, nickel sulfate provides sufficient nickel ions to ensure the thickness and quality of the coating; sodium hypophosphite is used as a reducing agent, and its proportion ensures sufficient reducing power to reduce nickel ions to metallic nickel; sodium citrate is used as a chelating agent to effectively stabilize the nickel ions in the plating solution and prevent them from premature precipitation; carbon nanotubes can optimize the light absorption and reflection characteristics of the coating, and work synergistically with other ingredients to improve the overall performance of the coating.

[0010] Optionally, the plating solution components also include 2-4 parts of nano titanium dioxide.

[0011] By adopting the above technical solution, 2-4 parts of nano titanium dioxide are added to the plating solution. Nano titanium dioxide has excellent optical properties and chemical stability. It works synergistically with carbon nanotubes to further enhance the composite coating's ability to absorb ultraviolet rays, improve the coating's optical stability in outdoor ultraviolet environments, and broaden the application scenarios of blackened stainless steel workpieces. For example, in outdoor camera module shielding components, it can effectively resist ultraviolet damage to the coating and extend the service life of the components.

[0012] Optionally, the carbon nanotubes are surface modified, and the specific method of surface modification of the carbon nanotubes is: Adding carbon nanotubes into anhydrous ethanol and ultrasonically dispersing them to obtain a carbon nanotube suspension; Add nitric acid to the carbon nanotube suspension to make the concentration of nitric acid reach 3-5 mol / L, stir and react at 50-60° C. for 2-3 hours, and centrifuge and wash to neutral after the reaction. The polydiallyldimethylammonium chloride is prepared into a solution with a concentration of 0.1-0.3 g / L, and the organic dye with a sulfonic acid group is prepared into a solution with a concentration of 0.05-0.1 g / L; Adding carbon nanotubes to a polydiallyldimethylammonium chloride solution, stirring and reacting at 20-25°C for 1-2 hours at a stirring speed of 200-300 r / min, centrifuging and washing after the reaction, then adding the carbon nanotubes to an organic dye solution with a sulfonic acid group, stirring and reacting for 1-2 hours, centrifuging and washing again, to obtain modified carbon nanotubes; The modified carbon nanotubes were vacuum dried at 60-80°C for 6-8 hours.

[0013] By adopting the above technical scheme, adding anhydrous ethanol for ultrasonic dispersion can effectively break the agglomeration of carbon nanotubes and make them evenly dispersed; adding nitric acid for oxidation treatment, introducing oxygen-containing functional groups on the surface of carbon nanotubes, increasing their surface activity, and facilitating subsequent modification. A double-layer structure is formed by alternating adsorption of polydiallyldimethylammonium chloride and organic dyes with sulfonic acid groups. Polydiallyldimethylammonium chloride is positively charged and adsorbs negatively charged carbon nanotubes and organic dyes through electrostatic action. This self-assembled structure increases the dispersibility of carbon nanotubes in the plating solution by more than 30%, and enhances its bonding force with the black nickel coating, so that the carbon nanotubes can be more evenly embedded in the coating, giving full play to its role in optimizing the performance of the coating. Vacuum drying at 60-80°C for 6-8 hours can remove moisture and impurities on the surface of carbon nanotubes, ensuring their stability in the plating solution and compatibility with other components.

[0014] Optionally, the workpiece is placed in the plating solution and assisted by a pulse current, wherein the pulse period of the pulse current is 0.1-0.5s and the pulse duty ratio is 30-50%.

[0015] By adopting the above technical solution, in the process of chemical plating, under conventional direct current, the deposition of ions in the plating solution on the electrode surface is relatively continuous and stable, and it is easy to form larger grains. When pulse current is used as an auxiliary, the pulse period is 0.1-0.5s and the pulse duty cycle is 30-50%, and the periodic change of the current makes the deposition process of ions also periodic. During the pulse conduction period, the ions are deposited quickly; during the pulse off period, the ions diffuse and adjust, inhibiting the continuous growth of the grains. This periodic deposition process refines the grains of the coating, and the refined grain size is significantly reduced compared with conventional direct current plating. The grain refinement of the coating brings about a significant improvement in hardness and wear resistance. From the perspective of microstructure, fine grains increase the number of grain boundaries. As defects in the crystal structure, grain boundaries have an obstructive effect on dislocation movement. When external force acts on the coating, dislocations are blocked at the grain boundaries, and a larger external force is required to cause the material to undergo plastic deformation, thereby increasing the hardness of the coating. In terms of wear resistance, the refined grains make the coating structure denser, reducing the shedding of abrasive particles and increased wear caused by pores and defects during the wear process.

[0016] Optionally, the blackened stainless steel workpiece is further subjected to ion implantation, wherein nitrogen ions are used for the ion implantation, and the energy of the ion implantation is 50-100 keV and the dose is (1-5)×10 16 ions / cm 2 .

[0017] By adopting the above technical solution, nitrogen ions are implanted into the blackened stainless steel workpiece surface with an energy of 50-100 keV and a dose of (1-5)×10¹ 6 ions / cm². Under the action of high energy, nitrogen ions hit the atoms on the surface of stainless steel at high speed, overcome the binding force between atoms, and enter the matrix. Nitrogen ions react chemically with iron, chromium and other elements in stainless steel to form nitrides with higher hardness, such as Fe 4 N, CrN, etc. These nitrides are evenly distributed on the surface layer of stainless steel, changing the surface structure and chemical composition. In terms of corrosion resistance, the formed nitrides have good chemical stability, which can prevent the direct contact between the corrosive medium and the stainless steel matrix, and play an isolation and protection role. In terms of surface hardness, the high hardness characteristics of nitrides significantly improve the surface hardness of stainless steel, enhance its ability to resist external scratches and wear, and improve the mechanical properties of the surface, so that the blackened stainless steel workpieces can show better durability and reliability in various application scenarios.

[0018] Optionally, the acidic activation solution components include 5-10% hydrofluoric acid, 10-15% nitric acid, 0.5-2% thiourea, 0.05-0.1% sodium dodecyl sulfate, and the rest is water in mass percentage, and the sensitizing solution components include 3-5% stannous chloride, 10-15% hydrochloric acid, 0.05-0.1% polyethylene glycol, and the rest is water.

[0019] By adopting the above technical scheme, in the acidic activation solution, 5-10% hydrofluoric acid reacts with the stainless steel surface to form micro-pits, increasing active sites; 10-15% nitric acid assists in oxidative etching to make the micro-pits more uniform and remove impurities and oxide films; 0.5-2% thiourea is used as a corrosion inhibitor to suppress excessive corrosion and maintain the mechanical properties of the substrate; 0.05-0.1% sodium dodecyl sulfate enhances wettability, allowing the activation solution to act evenly on the stainless steel surface, improving the consistency of the activation effect, and laying a good foundation for subsequent sensitization and chemical plating.

[0020] In the sensitizing solution, 3-5% stannous chloride provides sufficient tin ions to form a catalytic active layer on the stainless steel surface; 10-15% hydrochloric acid provides an acidic environment to prevent the hydrolysis of tin ions and promote their adsorption and activation on the stainless steel surface; 0.05-0.1% polyethylene glycol has a dispersing effect, making the tin ions more evenly dispersed in the solution, and then more evenly adsorbed on the stainless steel surface, improving the sensitization effect and ensuring the smooth progress of chemical plating and the quality of the coating.

[0021] In a second aspect, the present application provides an application of a chemical blackening process for stainless steel, using the following technical solution: An application of a chemical blackening process for stainless steel, wherein the chemical blackening process is applied to camera module shielding components and millimeter wave radar reflection components for surface blackening treatment.

[0022] By adopting the above technical solution, after applying the blackening process on the shielding parts of the camera module, the stray light suppression rate reached more than 98%, the imaging clarity was improved by 30%, and the color reproduction error was reduced to less than 5%, effectively improving the image quality. After the blackening treatment, the reflection efficiency of the millimeter-wave radar reflective parts increased by 25%, the detection accuracy increased by 15%, and the maximum detection distance increased by 20%, significantly enhancing the overall performance of the millimeter-wave radar system. After 1,000 hours of durability testing in harsh environments such as high and low temperatures (-40℃-80℃) and high humidity (95%RH), the surface blackening layer of the treated stainless steel parts did not fall off or discolor, and the performance remained stable.

[0023] In summary, this application has the following beneficial effects: 1. The process of the present application, through the impact force generated by ultrasonic cavitation, the saponification reaction of alkaline additives and oil stains, and the synergistic effect of surfactants to reduce interfacial tension, thoroughly removes oil stains on the surface of stainless steel, providing a clean surface for subsequent processes. Then, it is immersed in an activation solution to form micro-pits to increase surface active sites, and immersed in a sensitizing solution to adsorb catalytically active tin ions to provide catalytic centers for chemical plating. Finally, the pH value of the plating solution is controlled at 4.8-5.2, and the temperature is maintained at 90-92°C for 1-2 hours to allow nickel sulfate, sodium hypophosphite, sodium citrate and other components to react stably, sodium hypophosphite reduces nickel ions to form a coating, and sodium citrate stabilizes nickel ions, thereby obtaining a uniform, dense black coating with good optical and electromagnetic properties.

[0024] 2. In the present application, it is preferred to add nitric acid for oxidation treatment in the surface modification process of carbon nanotubes, introduce oxygen-containing functional groups on the surface of carbon nanotubes, improve surface activity, and create conditions for subsequent modification. Subsequently, prepare a polydiallyldimethylammonium chloride solution and a solution of an organic dye with a sulfonic acid group, stir and react the carbon nanotube suspension with the two in turn, and use electrostatic action to alternately adsorb to form a self-assembled structure, so that the dispersibility of carbon nanotubes in the plating solution is increased by more than 30%, and the binding force with the black nickel coating is enhanced to ensure that it is evenly embedded in the coating to optimize the coating performance.

[0025] 3. The method of the present application adopts pulse current to assist in the chemical plating process, so that the ion deposition is periodic, with rapid deposition in the on period and diffusion adjustment in the off period, thereby inhibiting the continuous growth of grains, reducing the grain size of the refined coating, and increasing the grain boundaries to hinder the dislocation movement, thereby improving the hardness and wear resistance; after blackening, the workpiece is then treated with nitrogen ion implantation, and the nitrogen ions react with stainless steel elements to form high-hardness nitrides, which are evenly distributed in the surface layer to change the organizational structure and composition, enhance corrosion resistance and surface hardness, and improve durability and reliability. DETAILED DESCRIPTION

[0026] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0027] Preparation Example 1 A surface modification method for carbon nanotubes: Weigh 1 kg of multi-walled carbon nanotubes with a purity of ≥98% and add them to 5 kg of anhydrous ethanol. Put the container containing the mixture of carbon nanotubes and anhydrous ethanol into an ultrasonic cleaner, set the ultrasonic power to 250 W, and perform ultrasonic dispersion for 45 minutes to form a carbon nanotube suspension.

[0028] The carbon nanotube suspension was transferred to the reactor, the stirring device was turned on, the stirring speed was set to 300r / min, concentrated nitric acid was added to the reactor, and the addition was stopped when the nitric acid concentration reached 4mol / L. The temperature of the reactor was adjusted to 55°C, and this temperature was maintained and the reaction was stirred for 2.5 hours. After the reaction was completed, the suspension in the reactor was transferred to a centrifuge and centrifuged at a speed of 10000r / min for 10 minutes, the supernatant was poured off, and the carbon nanotubes were passed through clean water until the pH value of the washing liquid was neutral.

[0029] Add deionized water to polydiallyldimethylammonium chloride to prepare a solution with a concentration of 0.2 g / L. Add deionized water to an organic dye with a sulfonic acid group to prepare a solution with a concentration of 0.08 g / L.

[0030] The washed carbon nanotubes were added to the polydiallyldimethylammonium chloride solution, and the reaction container was placed on a magnetic stirrer, the temperature was set to 25°C, the stirring speed was 250r / min, and the reaction was stirred for 1.5 hours to form a first adsorption layer. After the reaction was completed, the solution was centrifuged to separate the carbon nanotubes modified with polydiallyldimethylammonium chloride, and deionized water was added for washing. The carbon nanotubes modified with polydiallyldimethylammonium chloride were then added to the organic dye solution with sulfonic acid groups, and the reaction was carried out for 1.5 hours under the same conditions to form a second adsorption layer, and the centrifugation and washing operations were performed again to obtain the surface-modified carbon nanotubes.

[0031] The surface-modified carbon nanotubes were placed in a vacuum drying oven, the temperature was set to 70°C, and the drying time was 7 hours.

[0032] Preparation Example 2 A method for surface modification of carbon nanotubes: The difference from Preparation Example 1 is that deionized water is added to polydiallyldimethylammonium chloride to prepare a solution with a concentration of 0.1 g / L. An organic dye with a sulfonic acid group is added to deionized water to prepare a solution with a concentration of 0.1 g / L.

[0033] Preparation Example 3 A method for surface modification of carbon nanotubes: The difference from Preparation Example 1 is that deionized water is added to polydiallyldimethylammonium chloride to prepare a solution with a concentration of 0.3 g / L. An organic dye with a sulfonic acid group is added to deionized water to prepare a solution with a concentration of 0.05 g / L.

[0034] Preparation Example 4 A surface modification method for carbon nanotubes: Weigh 1 kg of multi-walled carbon nanotubes with a purity of ≥98% and add them to 5 kg of anhydrous ethanol. Put the container containing the mixture of carbon nanotubes and anhydrous ethanol into an ultrasonic cleaner, set the ultrasonic power to 250 W, and perform ultrasonic dispersion for 45 minutes to form a carbon nanotube suspension.

[0035] Add deionized water to polydiallyldimethylammonium chloride to prepare a solution with a concentration of 0.2 g / L. Add deionized water to an organic dye with a sulfonic acid group to prepare a solution with a concentration of 0.08 g / L.

[0036] The washed carbon nanotubes were added to the polydiallyldimethylammonium chloride solution, and the reaction container was placed on a magnetic stirrer, the temperature was set to 25°C, the stirring speed was 250r / min, and the reaction was stirred for 1.5 hours to form a first adsorption layer. After the reaction was completed, the solution was centrifuged to separate the carbon nanotubes modified with polydiallyldimethylammonium chloride, and deionized water was added for washing. The carbon nanotubes modified with polydiallyldimethylammonium chloride were then added to the organic dye solution with sulfonic acid groups, and the reaction was carried out for 1.5 hours under the same conditions to form a second adsorption layer, and the centrifugation and washing operations were performed again to obtain the surface-modified carbon nanotubes.

[0037] The surface-modified carbon nanotubes were placed in a vacuum drying oven, the temperature was set to 70°C, and the drying time was 7 hours.

[0038] Example 1, a chemical blackening process for stainless steel: Sodium dodecylbenzene sulfonate and sodium hydroxide are dissolved in deionized water, the content of sodium dodecylbenzene sulfonate is 10g / L, and the content of sodium hydroxide is 25g / L, to obtain a degreasing agent. The stainless steel workpiece is placed in the degreasing agent, the ultrasonic frequency is set to 45kHz, the temperature is controlled at 60°C, and the treatment time is 20 minutes. After the degreasing treatment is completed, the workpiece is taken out of the degreasing solution and rinsed with deionized water.

[0039] The degreased workpiece is immersed in an acidic activation solution, which contains 8% hydrofluoric acid, 12% nitric acid, 1.4% thiourea, 0.08% sodium dodecyl sulfate, and the rest is water, at room temperature for 45 minutes. After the activation treatment is completed, the workpiece is removed from the activation solution and rinsed with deionized water to remove the residual activation solution on the surface.

[0040] Put the activated workpiece into the sensitizing solution, which includes 4% stannous chloride, 12% hydrochloric acid, 0.08% polyethylene glycol, and the rest is water. The temperature of the sensitizing solution is controlled at 70°C and soaked for 50 minutes. After the sensitization treatment is completed, take the workpiece out of the sensitizing solution and rinse it with deionized water to remove the residual sensitizing solution on the surface.

[0041] Add 3kg nickel sulfate, 2.5kg sodium hypophosphite, 1.2kg sodium citrate, and 0.4kg carbon nanotubes to 50kg deionized water, and stir at a stirring speed of 400r / min for 15min to obtain a plating solution. Use a pH meter to measure the pH value of the plating solution, and control the pH value of the plating solution to 4.8-5.2 by adding dilute sulfuric acid or sodium hydroxide solution. Put the plating solution into a heating device, control the temperature at 91±1℃, and turn on the stirring device to heat the plating solution evenly.

[0042] The sensitized workpiece was placed in the plating solution, and the stirring speed was maintained at 200r / min for plating for 1.5 hours. After the plating was completed, the workpiece was taken out of the plating solution and rinsed with deionized water to remove the residual plating solution on the surface. The workpiece was dried in a vacuum drying oven at 60°C to obtain a blackened stainless steel workpiece.

[0043] Example 2, a chemical blackening process for stainless steel: The difference from Example 1 is that 2.5 kg of nickel sulfate, 2 kg of sodium hypophosphite, 1 kg of sodium citrate, and 0.2 kg of carbon nanotubes are added to 40 kg of deionized water, and stirred at a stirring speed of 400 r / min for 15 minutes to obtain a plating solution.

[0044] Example 3, a chemical blackening process for stainless steel: The difference from Example 1 is that 3.5 kg of nickel sulfate, 3 kg of sodium hypophosphite, 1.5 kg of sodium citrate, and 0.6 kg of carbon nanotubes are added to 60 kg of deionized water, and stirred at a stirring speed of 400 r / min for 15 minutes to obtain a plating solution.

[0045] Example 4, a chemical blackening process for stainless steel: The difference from Example 1 is that 3kg of nickel sulfate, 2.5kg of sodium hypophosphite, 1.2kg of sodium citrate, 0.4kg of carbon nanotubes, and 0.3kg of nano-titanium dioxide are added to 50kg of deionized water, and stirred at a stirring speed of 400r / min for 15min to obtain a plating solution.

[0046] Example 5, a chemical blackening process for stainless steel: The difference from Example 1 is that the carbon nanotubes in the plating solution are surface-modified and prepared by Preparation Example 1.

[0047] Example 6, a chemical blackening process for stainless steel: The difference from Example 5 is that the carbon nanotubes in the plating solution are surface-modified and prepared by Preparation Example 2.

[0048] Example 7, a chemical blackening process for stainless steel: The difference from Example 5 is that the carbon nanotubes in the plating solution are surface-modified and prepared by Preparation Example 3.

[0049] Example 8, a chemical blackening process for stainless steel: The difference from Example 1 is that the workpiece after sensitization treatment is placed in the plating solution, and the plating is carried out at a stirring speed of 200r / min.

[0050] Set the pulse period of the pulse power supply to 0.3s, the pulse duty cycle to 40%, the initial current density to 1.5A / dm², fix the anode graphite electrode to one side of the plating tank, and ensure that the anode electrode is in full contact with the plating solution. The stainless steel workpiece is used as the cathode and fixed in the plating tank with a fixture. Turn on the pulse power switch to apply the pulse current.

[0051] The plating time is 1.5 hours. After the plating is completed, the pulse power supply is turned off at the same time, the workpiece is taken out of the plating solution, and rinsed with deionized water to remove the residual plating solution on the surface. The workpiece is dried in a vacuum drying oven at 60°C to obtain a blackened stainless steel workpiece.

[0052] Example 9, a chemical blackening process for stainless steel: The difference from Example 8 is that the pulse period of the pulse power supply is set to 0.1 s, and the pulse duty cycle is set to 30%.

[0053] Example 10, a chemical blackening process for stainless steel: The difference from Example 8 is that the pulse period of the pulse power supply is set to 0.5s, and the pulse duty cycle is set to 50%.

[0054] Example 11, a chemical blackening process for stainless steel: The difference from Example 8 is that: Place the blackened stainless steel workpiece on the sample stage of the ion implanter, close the door of the implantation chamber, and perform a sealing check. Start the vacuum system and pre-evacuate the chamber to 10 -5 -10 -6 Pa magnitude; The nitrogen gas with purity ≥98% was passed through the extraction system of the ion source to extract the nitrogen ion beam and accelerate it to 80keV. The sample stage was started to rotate so that the surface of the workpiece was evenly implanted with ions. The dose of ion implantation was recorded in real time to ensure that the implantation dose reached 3×10 16 ions / cm².

[0055] Example 12, a chemical blackening process for stainless steel: The difference from Example 11 is that the nitrogen ion beam is extracted and accelerated to 50 keV, and the implantation dose reaches 1×10 16 ions / cm².

[0056] Example 13, a chemical blackening process for stainless steel: The difference from Example 11 is that the nitrogen ion beam is extracted and accelerated to 100 keV, and the implantation dose reaches 5×10 16 ions / cm².

[0057] Comparative Example 1 A chemical blackening process for stainless steel: The difference from Example 1 is that no activation treatment and sensitization treatment are performed.

[0058] Comparative Example 2 A chemical blackening process for stainless steel: The difference from Example 1 is that the pH value of the plating solution is controlled at 4.3-4.7.

[0059] Comparative Example 3 A chemical blackening process for stainless steel: The difference from Example 1 is that the pH value of the plating solution is controlled at 5.3-5.7.

[0060] Comparative Example 4 A chemical blackening process for stainless steel: The difference from Example 5 is that the carbon nanotubes in the plating solution are prepared by Preparation Example 4.

[0061] Comparative Example 5 A stainless steel processing technology: Sodium dodecylbenzene sulfonate and sodium hydroxide are dissolved in deionized water, the content of sodium dodecylbenzene sulfonate is 10g / L, and the content of sodium hydroxide is 25g / L, to obtain a degreasing agent. The stainless steel workpiece is placed in the degreasing agent, the ultrasonic frequency is set to 45kHz, the temperature is controlled at 60°C, and the treatment time is 20 minutes. After the degreasing treatment is completed, the workpiece is taken out of the degreasing solution and rinsed with deionized water to obtain a degreased stainless steel workpiece.

[0062] Performance test test method 1. Stray light suppression rate test Test equipment: integrating sphere (with built-in xenon lamp standard light source), spectrometer (wavelength range 200-1100nm), high-precision optical power meter.

[0063] The blackened stainless steel parts were cut into 10 mm × 10 mm sizes, and the surface was clean and free of contaminants.

[0064] Place a standard reflective white plate (reflectivity ≥ 99%) in the integrating sphere and record the reference light intensity value. Remove the white plate, put in the sample to be tested, and adjust the angle between the sample and the light source to 45°. The light source emits the full spectrum and measures the output light intensity of the integrating sphere.

[0065] Calculate the stray light suppression rate: Suppression rate = (1-I sample / I ref )*100%.

[0066] Repeat the test 3 times and take the average value.

[0067] (II) Millimeter wave reflection efficiency test Test equipment: vector network analyzer (Keysight N5245A), millimeter wave horn antenna (frequency coverage 24-77 GHz), anechoic chamber (background noise ≤ -60 dB), three-dimensional positioning platform (accuracy ±0.1 mm).

[0068] The blackened part is processed into a standard reflector (size ≥ 10λ, λ is the wavelength) and fixed to the bracket. The VNA is calibrated using a standard gain horn antenna to eliminate cable loss. The reflection coefficient of the empty anechoic chamber is recorded.

[0069] The sample was placed 1m in front of the antenna with an incident angle of 0°. The frequency range was scanned from 24 to 77 GHz and the reflection coefficient was recorded.

[0070] Calculate reflection efficiency: Reflection efficiency = [(S 11 sample -S 11 bg ) / (1-S 11 bg )] 2 *100%.

[0071] (III) Corrosion resistance test Standard: ASTM D6869; Conditions: 10*10cm sample; Stage 1: salt spray (5% NaCl) for 2 hours; Stage 2: drying (40°C, 0%RH) for 4 hours; Stage 3: damp heat (50°C, 95%RH) for 18 hours; Cycle period: 24 hours; Total time: 1000 hours.

[0072] After the test, check the coating morphology on the sample surface.

[0073] Table 1 Experimental data

[0074] Combining Example 1 and Comparative Example 1 and Table 1, it can be seen that in Comparative Example 1, no activation treatment and sensitization treatment were performed, and its stray light suppression rate was 94.6%, the millimeter wave reflection efficiency was 91.7%, and the coating was damaged and peeled off in the salt spray test; while the stray light suppression rate of Example 1 was 97.9%, the millimeter wave reflection efficiency was 94.8%, and the coating was not damaged or peeled off in the salt spray test. This shows that activation treatment and sensitization treatment can increase the active sites on the surface of stainless steel, adsorb catalytically active tin ions, provide a good foundation for chemical plating, make the coating more uniform and dense, thereby improving the stray light suppression rate and millimeter wave reflection efficiency, and enhancing the corrosion resistance of the coating.

[0075] Combining Example 1 and Comparative Examples 2-3 and Table 1, it can be seen that Comparative Example 2 controls the pH value of the plating solution at 4.3-4.7, and Comparative Example 3 controls the pH value of the plating solution at 5.3-5.7. Their stray light suppression rate and millimeter wave reflection efficiency are lower than those of Example 1 (the pH value of the plating solution is controlled at 4.8-5.2), and the coating is damaged and peeled off in the salt spray test. This shows that the appropriate pH value of the plating solution (4.8-5.2) is crucial to ensure the stability of the plating solution and the high efficiency of the reaction. Within this pH value range, the components in the plating solution can undergo a stable chemical reaction to form a uniform and dense coating, thereby improving the optical properties and corrosion resistance of the product. When the pH value deviates from this range, the stability of the plating solution is affected and the quality of the coating decreases.

[0076] Combining Example 5 and Comparative Example 4 with Table 1, it can be seen that the carbon nanotubes in the plating solution of Example 5 are surface modified by Preparation Example 1, and the carbon nanotubes in the plating solution of Comparative Example 4 are prepared by Preparation Example 4 (the difference from Preparation Example 1 is that the nitric acid oxidation treatment step is missing). The stray light suppression rate of Example 5 is 98.9%, the millimeter wave reflection efficiency is 95.9%, and the coating is not damaged or peeled off in the salt spray test; the stray light suppression rate of Comparative Example 4 is 98.1%, the millimeter wave reflection efficiency is 95.2%, and the coating is damaged and peeled off in the salt spray test. This shows that the nitric acid oxidation treatment step of the carbon nanotubes can introduce oxygen-containing functional groups on their surface, increase surface activity, and through subsequent layer-by-layer self-assembly modification, the carbon nanotubes have better dispersibility in the plating solution and stronger bonding with the black nickel coating, thereby improving the optical properties and corrosion resistance of the product. The lack of this step will result in less than ideal bonding between the carbon nanotubes and the coating, and a decrease in performance.

[0077] Combining Example 1 and Comparative Example 5 with Table 1, it can be seen that Comparative Example 5 was only subjected to degreasing treatment, and its stray light suppression rate was 63.5%, and its millimeter wave reflection efficiency was 76.9%, which were much lower than those of Example 1. This fully demonstrates that the activation, sensitization, and chemical plating steps in the chemical blackening process play a key role in improving the stray light suppression rate and millimeter wave reflection efficiency of stainless steel parts, and only degreasing treatment cannot form a blackened coating with good performance.

[0078] It can be seen from Examples 1-4 and Table 1 that by adjusting the contents of nickel sulfate, sodium hypophosphite, sodium citrate, carbon nanotubes and other components in the plating solution, Examples 1-3 have certain fluctuations in the stray light suppression rate and millimeter wave reflection efficiency compared with Example 1, but the overall performance is good, and the coatings in the salt spray test are not damaged or peeled off. This shows that the proportions of the various components in the plating solution of the present application can work synergistically to ensure the quality and performance of the coating. Nano-titanium dioxide has excellent optical properties and chemical stability. It works synergistically with carbon nanotubes to further enhance the composite coating's ability to absorb ultraviolet rays and improve the optical stability of the coating in ultraviolet environments such as outdoors.

[0079] Combining Example 1 and Examples 5-7 with Table 1, it can be seen that the carbon nanotubes in the plating solution of Examples 5-7 are surface-modified by different preparation examples (Preparation Examples 1-3), and compared with Example 1 (no surface-modified carbon nanotubes are used), the stray light suppression rate and millimeter wave reflection efficiency are improved, and the salt spray test coating is not damaged or peeled. This shows that surface modification of carbon nanotubes, forming a multilayer structure through layer-by-layer self-assembly, can significantly improve the dispersibility of carbon nanotubes in the plating solution, enhance its bonding with the black nickel coating, thereby optimizing the performance of the coating, further improving the stray light suppression rate and millimeter wave reflection efficiency of the product, and at the same time does not affect the corrosion resistance of the coating.

[0080] Combining Example 1 and Examples 8-10 and Table 1, it can be seen that Examples 8-10 use pulse current assistance during the plating process, and the pulse period and pulse duty cycle are different. Compared with Example 1 (without pulse current assistance), the stray light suppression rate and millimeter wave reflection efficiency are improved, and the salt spray test coating is not damaged or peeled. This shows that by using pulse current assistance in the chemical plating process, by controlling the pulse period and pulse duty cycle, the ion deposition process can be optimized, the coating grains can be refined, and the hardness and wear resistance of the coating can be improved. At the same time, the optical properties of the product are also improved, so that the stray light suppression rate and millimeter wave reflection efficiency are improved, and the corrosion resistance of the coating is not affected.

[0081] Combining Example 1 and Examples 11-13 with Table 1, it can be seen that Examples 11-13 perform nitrogen ion implantation treatments with different energies and doses on the blackened stainless steel workpieces. Compared with Example 1, the stray light suppression rate and millimeter wave reflection efficiency are further improved, and the coating is not damaged or peeled off in the salt spray test. This shows that nitrogen ion implantation can form nitrides with higher hardness on the surface of stainless steel, change the surface structure and chemical composition, thereby improving the corrosion resistance and surface hardness of the coating, and also has a positive effect on the optical properties of the product, further improving the stray light suppression rate and millimeter wave reflection efficiency.

[0082] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A chemical blackening process for stainless steel, characterized in that: The following steps are involved: Place the stainless steel workpiece in a solution containing a surfactant and an alkaline additive for degreasing, and treat it at 40-50kHz ultrasonic waves and 55-65℃ for 15-30 minutes; Immerse the degreased workpiece in the activation solution for 40-50 minutes at room temperature, then put the workpiece into the sensitizing solution for 40-60 minutes at 60-80℃; The plating solution comprises nickel sulfate, sodium hypophosphite, sodium citrate and carbon nanotubes. The pH value of the plating solution is controlled at 4.8-5.2 and the temperature is 90-92° C. The workpiece is placed in the plating solution and a blackened stainless steel workpiece is obtained after plating for 1-2 hours.

2. The chemical blackening process of stainless steel according to claim 1, characterized in that: The plating solution components include 25-35 parts of nickel sulfate, 20-30 parts of sodium hypophosphite, 10-15 parts of sodium citrate, 2-6 parts of carbon nanotubes, and 400-600 parts of deionized water in parts by weight.

3. The chemical blackening process of stainless steel according to claim 1, characterized in that: The plating solution components also include 2-4 parts of nano titanium dioxide.

4. The chemical blackening process of stainless steel according to claim 1, characterized in that: The carbon nanotubes are surface modified, and the specific method of surface modification of the carbon nanotubes is: Adding carbon nanotubes into anhydrous ethanol and ultrasonically dispersing them to obtain a carbon nanotube suspension; Add nitric acid to the carbon nanotube suspension to make the concentration of nitric acid reach 3-5 mol / L, stir and react at 50-60° C. for 2-3 hours, and centrifuge and wash to neutral after the reaction. The polydiallyldimethylammonium chloride is prepared into a solution with a concentration of 0.1-0.3 g / L, and the organic dye with a sulfonic acid group is prepared into a solution with a concentration of 0.05-0.1 g / L; Adding carbon nanotubes to a polydiallyldimethylammonium chloride solution, stirring and reacting at 20-25°C for 1-2 hours at a stirring speed of 200-300 r / min, centrifuging and washing after the reaction, then adding the carbon nanotubes to an organic dye solution with a sulfonic acid group, stirring and reacting for 1-2 hours, centrifuging and washing again, to obtain modified carbon nanotubes; The modified carbon nanotubes were vacuum dried at 60-80°C for 6-8 hours.

5. The chemical blackening process of stainless steel according to claim 1, characterized in that: The workpiece is placed in the plating solution and pulse current is used as an aid, wherein the pulse period of the pulse current is 0.1-0.5s and the pulse duty ratio is 30-50%.

6. The chemical blackening process of stainless steel according to claim 1, characterized in that: The blackened stainless steel workpiece is also subjected to ion implantation, wherein nitrogen ions are used in the ion implantation, and the energy of the ion implantation is 50-100 keV and the dose is (1-5)×10 16 ions / cm 2 .

7. The chemical blackening process of stainless steel according to claim 1, characterized in that: The activation solution components include 5-10% hydrofluoric acid, 10-15% nitric acid, 0.5-2% thiourea, 0.05-0.1% sodium dodecyl sulfate, and the rest is water in terms of mass percentage. The sensitizing solution components include 3-5% stannous chloride, 10-15% hydrochloric acid, 0.05-0.1% polyethylene glycol, and the rest is water.

8. An application of the chemical blackening process of stainless steel as claimed in any one of claims 1 to 7, characterized in that: The chemical blackening process is applied to camera module shielding components and millimeter wave radar reflection components for surface blackening treatment.

Citation Information

Patent Citations

  • Method for preparing highly wear-resistant and corrosion-resistant carbon nano tube / graphene reinforced nickel-phosphorus based composite coating

    CN103695877A

  • Chemical plating solution, preparation method of chemical plating solution, Ni-P-Gr chemical plating layer and preparation method and application of Ni-P-Gr chemical plating layer

    CN119392227A